Aquatic plyometric training increases vertical jump in female volleyball players - Martel, G. F.; Harmer, M. L.; Logan, J. M.; Parker, C. B. (Medicine & Science in Sports & Exercise, 2005)
Purpose: Numerous studies have reported that land-based plyometrics can improve muscular strength, joint stability, and vertical jump (VJ) in athletes; however, due to the intense nature of plyometric training, the potential for acute muscle soreness or even musculoskeletal injury exists. Performance of aquatic plyometric training (APT) could lead to similar benefits, but with reduced risks due to the buoyancy of water. Unfortunately, there is little information regarding the efficacy of APT. Thus, the purpose of this study was to examine the effects of APT on VJ and muscular strength in volleyball players.